Feasibility and cost effectiveness of ambulatory laparoscopic cholecystectomy. A retrospective cohort study. (July 2020) - Manzia, Tommaso Maria; Quaranta, Claudia; Filingeri, Vincenzino; Toti, Luca; Anselmo, Alessandro; Tariciotti, Laura; De Carolis, Gerardo; Cacciola, Roberto; Di Lorenzo, Nicola; Sorge, Roberto; Angelico, Roberta; Monteleone, Giovanni; et al.
Abstract: Background: Ambulatory surgery is an efficient, safe and widely performed procedure; this study would shows the advantages of the ambulatory laparoscopic cholecystectomy procedure from the point of view of patients and the Hospital/National Health System. Materials and Methods : Single-center retrospective cohort study including 288 patients who underwent laparoscopic-cholecystectomy at **** from January 2016 to July 2018. Ambulatory LC were compared to well-matched inpatient procedures performed in the same study period. The primary endpoints was the 30-day readmission rate. Secondary endpoints were the discharge rate in the ambulatory group, the post-operative complications rate and cost effectiveness. Results: 120/288 (41.7%) patients underwent ambulatory laparoscopic cholecystectomy. Thirty-two (26.7%) patients who underwent ambulatory laparoscopic cholecystectomy had major preoperative comorbidities and 35 (29.2%) had undergone prior abdominal surgery. The readmission rates for ambulatory patients and inpatients were 0.8% and 1.7% (p = 0.56), respectively; 104 (86.7%) ambulatory patients were discharged successfully on the same day. The two groups showed the same post-operative complication rate (p = 0.40). Ambulatory procedures resulted in related cost savings of more than 300% for the hospital and a remarkable financial benefit for the National Italian Healthcare System, accounting for savings exceeding € 27 000 per year. Conclusions: Ambulatory laparoscopic cholecystectomy is safe and cost effective. Since a third of ambulatory patients showed comorbidity or previous abdominal surgery, we believe that this procedure may be performed safely in a tertiary HPB centre, even in complex patients. Highlights: Ambulatory laparoscopic cholecistectomy is an efficient, safe and feasible procedure. Ambulatory Laparoscopic cholecistectomy may also be offered to complex patients. Ambulatory laparoscopic cholecystectomy is cost effective for both Hospital and National Health System.